Management of castration resistant prostate cancer - Eisenberger, Mario A.; Saad, Fred (Current Clinical Urology,, 2014)
This volume provides new data about the molecular biology of CRPC and a review of the definition, staging and prognostic factors that define CRPC. The book features an in-depth review of proven therapeutic options, including bone-targeted therapies, immunotherapy, chemotherapy and hormonal based therapies. Combination therapy as well as novel targeted approaches presently under investigation are also reviewed. The text provides up-to-date guidelines and algorithms for the management of CRPC based on international guidelines presently available as well as evidence-based medicine. As a concise yet comprehensive summary of the current status of the field, Management of Castration Resistant Prostate Cancer serves as a very useful resource for physicians and researchers dealing with this challenging malignancy.